COVID-19: A Single-Center ICU Experience of the First Wave in the Philippines. (1st February 2021) - Ubaldo, Onion Gerald V.; Palo, Jose Emmanuel M.; Cinco, Jude Erric L.
Abstract : On January 30, 2020, the WHO declared the novel coronavirus of 2019 a pandemic, causing millions of cases and thousands of deaths worldwide, exposing the vulnerabilities of healthcare systems around the world with each country having its own experience. These ranged from patient clinical profiles to management recommendations and to government interventions. There is a paucity of published data regarding Philippine experience. This study is a retrospective, descriptive study of ninety-one COVID-19 probable patients admitted in the COVID ICU of The Medical City from March 16 to May 7, 2020. We described clinical and demographic characteristics amongst COVID-19-confirmed and -negative patients. Therapeutic interventions including COVID-19 investigational drug use and other organ failure strategies were noted and tested for association with ICU survivors and nonsurvivors. We observed that there was no therapeutic intervention that was associated with improved outcomes, with some interventions showing trends favoring the ICU nonsurvivor group. These interventions include, but are not limited to, the use of hydroxychloroquine and tocilizumab, and prone positioning. We also observed that a higher SAPS-3 score was associated with the COVID-19 positive group and the ICU nonsurvivor group. On PubMed search, there seems to be no Philippine-specific literature regarding COVID-19 ICU experience. Further investigations to include more variables are recommended.